Keefektifan Model Pembelajaran Think Pair Share Terhadap Sikap Belajar dan Hasil Belajar Siswa Pada Tema 2 Sub Tema 1 Sumber Energi Siswa Kelas IV SDN Kutosari Kabupaten Pekalongan - Muhammad Amirul Akrom Muttaqin (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
This research is motivated by learning is still not optimal because the learning done by teachers watching and less creative, so that students are less active, quick to feel bored and the use of media and learning resources are still lacking. Student data obtained by students who actively participated in the learning there are only a few students. The problem formulation in this study is: is the TPS Learning model (Think Pair Share) effective against student learning attitudes on theme 2, sub theme 1. Energy Source of Grade 4 students at SDN Kutosari Pekalongan?, is the TPS Learning Model (Think Pair Share) effective for students' learning outcomes in theme 2, sub-theme 1. Energy Source for Grade 4 students at SDN Kutosari, Pekalongan Regency? This type of research is experimental research. The research plan with the design used is One Group Pre Test and Post Test. The samples in this study were all grade 4 students at SDN Kutosari, Pekalongan Regency. Data analysis techniques using t-test. The results obtained student learning attitude in the pre-test class obtained an average of 67 with less criteria. Students' learning attitudes in post-test classes were obtained by an average of 82 with good criteria. The result of t test calculation obtained thitung = 4,225. From the distribution list t with dk = n -1 = 20– 1 = 19 obtained 1,729. Because 4,225 > 1,729 then Ho was rejected, so it can be concluded that there is effectiveness of TPS Learning Model (Think Pair Share) on Learning Attitudes and Student Learning Outcomes in Theme 2, Sub Theme 1. Energy Resources for Grade 4 students at SDN Kutosari, Pekalongan Regency. The advice that can be produced in this research is that teachers in carrying out assessments pay attention to the Think Pair Share learning model used so as to improve student attitudes and learning outcomes.